2015
DOI: 10.1007/s11060-015-1841-y
|View full text |Cite
|
Sign up to set email alerts
|

Pre-radiation lymphocyte harvesting and post-radiation reinfusion in patients with newly diagnosed high grade gliomas

Abstract: Radiation (RT), temozolomide (TMZ), and dexamethasone in newly diagnosed high grade gliomas (HGG) produces severe treatment-related lymphopenia (TRL) that is associated with early cancer-related deaths. This TRL may result from inadvertent radiation to circulating lymphocytes. This study reinfused lymphocytes, harvested before chemo-radiation, and assessed safety, feasibility, and trends in lymphocyte counts. Patients with newly diagnosed HGG and total lymphocyte counts (TLC) ≥ 1000 cells/mm3 underwent apheres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 29 publications
3
28
0
Order By: Relevance
“…Campian et al 21 reported similar results in human GB/anaplastic astrocytoma where pre-radiation lymphocyte harvesting followed by reinfusing these nonirradiated lymphocytes after radiation session did not significantly ameliorate lymphopenia. G-CSF actively suppresses BM lymphocytopoiesis in mice.…”
Section: Elevated G(m)-csf Is Immunosuppressive In Gbmentioning
confidence: 72%
“…Campian et al 21 reported similar results in human GB/anaplastic astrocytoma where pre-radiation lymphocyte harvesting followed by reinfusing these nonirradiated lymphocytes after radiation session did not significantly ameliorate lymphopenia. G-CSF actively suppresses BM lymphocytopoiesis in mice.…”
Section: Elevated G(m)-csf Is Immunosuppressive In Gbmentioning
confidence: 72%
“…A recent study at Johns Hopkins University investigated the utility of reinfusing harvested pre-treatment circulating lymphocytes after radiation [36]. The use of exogenous Interleukin-7 is being studied in high grade gliomas by the Adult Brain Tumor Consortium and the Cancer Therapy Evaluation Program because a recent study showed that patients with high-grade gliomas did not have the expected IL-7 physiologic elevation in response to radiation-induced lymphopenia [37].…”
Section: Discussionmentioning
confidence: 99%
“…This iatrogenic lymphopenia was not taken seriously until subsequent evidences indicated that patients with lowered peripheral lymphocyte counts (PLCs) suffered early death from tumor progression . Recent studies have brought attention to the treatment‐related lymphopenia observed in glioma patients . As the standard of care for gliomas, radiotherapy (RT), steroids, and temozolomide (TMZ) are well‐documented lymphotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…This comprehensive therapy modality causes 40% of high‐grade glioma (HGG) patients to develop severe lymphopenia (grade III‐IV toxicity) within 2 months after course initiation . The state of immunosuppression is persistent and detrimentally affects patients with increased susceptibility to opportunistic infections, additional risk of secondary central nervous system (CNS) tumors, and deteriorated survival time …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation